Assessment of the credit risk management practices of National Investment Bank Ltd. - Aidoo, Monica (2016)
A Thesis submitted to the Department of Accounting and Finance, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the degree of Master of Business Administration (Accounting Option)